Stakeholders' Perceptions of the Outcomes of Translocated Eland in Nyae Nyae Conservancy, Namibia - Lendelvo, Selma; Suich, Helen; Mfune, John K. E. (Frontiers in Conservation Science, 2022)
Translocation of wildlife species from one area to another is a conservation tool that contributes to the restoration of depleted populations, augment declining populations or establishment of new populations. This paper documents one of the first studies examining in detail the perceptions of stakeholders about the factors influencing the outcomes of translocations of wildlife into a community conservation area, using the case of eland (Taurotragus oryx) translocations into the Nyae Nyae Conservancy in Namibia. The translocations took place between 2000 and 2005 as part of the national community-based natural resource management programme and monitored through annual waterpoint counts. These data on perceptions were collected through a household survey and focussed group discussions involving community members and leaders and key-informant interviews with external stakeholders. Community members’ perceptions could not confirm that the translocated eland decreased or increased, however, reflected that eland individuals have moved away from the release site soon after translocation to more distant locations further away from human settlements. The outcomes of the translocations were perceived to be most strongly associated with anthropogenic factors compared to habitat or environmental factors. However, stakeholders exhibited divergent perceptions regarding which of the anthropogenic factors was of most importance, particularly with respect to the roles of the different types of hunting, and to a lesser degree, the role of traditional burning of landscapes on translocation outcomes. The paper illustrates the complexities associated with translocations of wildlife into community conservation areas compared to state protected areas, given the strong influence of human disturbances on translocation success. It highlights the importance of understanding the social factors influencing how and why translocated individuals may adapt well or poorly to their new environment. Building this understanding is essential to improving the outcomes of similar translocations in the future.